Immune Response Indicators in Term and Preterm Premature Rupture of Membranes: A Leukocyte Profile Evaluation - Septiyono, Eka Afdi; Luthfiana Zaki, Nissa; Rahmawati, Iis; Kurniawati, Dini (Universitas STRADA Indonesia, 2026)
Background: Premature rupture of membranes (PRM) occurs when membranes rupture spontaneously before delivery. PRM is categorized into preterm PRMor preterm premature rupture of membranes (PPROM), occurring before and at 37 weeks of gestation, and term PRM or premature rupture of membranes (PROM), occurring after 37 weeks. Objective: This study aimed to determine differences in leukocyte profiles between term and preterm PRM cases at RSD dr. Soebandi Jember. Methods: This research used an observational analytic design. This research involved two groups of pregnant women with term and preterm PRM. A total of 55 participants were included, with 28 in the preterm PRM group and 27 in the term PRM group. Data were collected from medical records between January 2023 and July 2024 using a purposive sampling technique. Normality tests were conducted using the Shapiro-Wilk Test. For normally distributed data (p > 0.05), the Independent T-Test was applied, while the Mann-Whitney Test was used for non-normally distributed data (p < 0.05). Results: The results showed no significant differences in lymphocyte (p-value=0,725) and neutrophil (p-value=0,893) levels. Similarly, no significant differences were found in leukocyte, monocyte, eosinophil, and basophil levels (p-values=0,987, 0,666, 0,949, and 0,979, respectively). Conclusion: The study showed no significant differences in the leukocyte profiles between term and preterm PRM. However, increased neutrophil counts in preterm cases may suggest an ongoing infection, highlighting the importance of monitoring leukocyte levels in PRM for potential infection risk management. Further studies are needed to assess how factors such as occupation and daily fatigue affect the incidence of PRM, especially in the preterm group.